Analysis of interleukin 7 and platelet-derived growth factor BB mRNA expression as potential markers in erythema nodosum leprosum - Fitri Kadarsih Banjar; Farida Tabri; Sri Vitayani Muchtar; Mochammad Hatta; Khaeruddin Djawad; Farida Ilyas; Sitti Musafirah; Muhammad Nasrum Massi; Agussalim Bukhari; Andi Alfian Zainuddin (PAGEPress Publications, 2023)
Introduction: Erythema Nodosum Leprosum (ENL) is an immunological complication of leprosy characterized by acute inflammation of the skin, nerves, and other organs. Identifying laboratory parameters are important to early diagnosis of leprosy reactions. Various cytokine biomarkers have been examined and only a few studies have reported on angiogenesis in leprosy. This study aims to understanding the pathomechanism of ENL by examined IL-7 and PDGF-BB mRNA expression that can be the development and consideration of new effective therapies to prevent reactions, recurrences, and defects in leprosy. Materials and Methods: The study used a cross-sectional analytic design. Sampling was done by peripheral blood from the patient and measuring mRNA expression with specific primers RT-PCR. Results: The expression of mRNA IL-7 and PDGF-BB was significantly different between multibasilar patients without reaction and with ENL reaction, where there was increased expression in ENL patients. This could be used as the development of potential biomarkers in ENL and development of new therapeutic intervention pathways in ENL.